VARIASI KECEPATAN FLUTTER PELAT TIPIS TERHADAP SUDUT DATANG ALIRAN - Jantje
One thin panel located under the influence of the air flow field at certain velocity exerts the pressure force, which is a function of time, on its surface. In accordance to the increment of the air flow velocity, at certain velocity limit, the panel encounters dynamic instability / flutter. Flutter of thin panel involves quite a large deformation, hence observation of non-linearity effect is considered. Analysis is made based on the finite elements method. The principle of virtual work is used to develop the equation of motion of a fluttering thin panel. The large deflection on the thin panel are follows the relationship between strain and displacement of Von-Karman, while the aerodynamic load is represented by the use of the quasi-steady first order piston theory. The equation of motion are solved by implementing the linearized updated mode with a non-linear time function (LUM/NTF). There will be two analytical observations, namely linear and non-linear approach. Analytical results yield to critical flutter-velocity for several boundary conditions of the panel as result of the air flow parallel to the panel surface and form an angle to one of its sides. Critical flutter values for rectangular thin panels at various boundary conditions (linear and nonlinear) and its variation with flow direction angle , length/width ratio and limit cycle amplitude are included in this thesis